Photoreflectance Spectroscopy Characterization of Ge/Si0.16Ge0.84 Multiple Quantum Wells on Ge Virtual Substrate - Hung-Pin Hsu; Pong-Hong Yang; Jeng-Kuang Huang; Po-Hung Wu; Ying-Sheng Huang; Cheng Li; Shi-Hao Huang; Kwong-Kau Tiong (Advances in Condensed Matter Physics)
We report a detailed characterization of a Ge/Si0.16Ge0.84 multiple quantum well (MQW) structure on Ge-on-Si virtual substrate (VS) grown by ultrahigh vacuum chemical vapor deposition by using temperature-dependent photoreflectance (PR) in the temperature range from 10 to 300 K. The PR spectra revealed a wide range of optical transitions from the MQW region as well as transitions corresponding to the light-hole and heavy-hole splitting energies of Ge-on-Si VS. A detailed comparison of PR spectral line shape fits and theoretical calculation led to the identification of various quantum-confined interband transitions. The temperature-dependent PR spectra of Ge/Si0.16Ge0.84 MQW were analyzed using Varshni and Bose-Einstein expressions. The parameters that describe the temperature variations of various quantum-confined interband transition energies were evaluated and discussed.